Application of geometric morphometric analyses to confirm three new wasps of Evaniidae (Hymenoptera: Evanioidea) from mid-Cretaceous Myanmar amber. (May 2020) - Shih, Peter J.M.; Li, Longfeng; Li, Daqing; Ren, Dong
Abstract: Evaniidae, commonly called 'ensign wasps' or 'hatchet wasps', comprise more than 21 described extant genera with over 449 species and an additional 17 extinct genera including 35 species from the Cretaceous and Paleogene deposits. Herein, Burmaevania gen. nov. with two new species B. brevis sp. nov and B. aequalis sp. nov, and a new species of Newjersevania rasnitsyni sp. nov. are described based on three well-preserved specimens from the mid-Cretaceous Myanmar (Burmese) amber. Besides morphological comparisons, forewings of nine described genera of Evaniidae and the three new species are studied by using the Geometric Morphometric Analyses (GMA) to confirm their state. urn:lsid:zoobank.org:pub:DBE8E565-5671-4B5A-93F2-8AEC6DA22A50.